Altered Gut Microbiota as an Auxiliary Diagnostic Indicator for Patients With Fracture-Related Infection - Xingqi Zhao; Xingqi Zhao; Wenli Tang; Haoyang Wan; Haoyang Wan; Zixin Lan; Hanjun Qin; Hanjun Qin; Qingrong Lin; Qingrong Lin; Yanjun Hu; Yanjun Hu; et al. (Frontiers in Microbiology, 2022)
Preoperative diagnosis of fracture-related infection (FRI) is difficult for patients without obvious signs of infection. However, specific profiles of gut microbiota may be used as a potential diagnostic tool for FRI as suggested by a previous study. The fecal microbiome was compared between 20 FRI patients (FRI group), 18 fracture healed patients (FH group), and 12 healthy controls (HC group) included after collection of fecal samples and evaluation. The α and β diversity indices were used to characterize the fecal microbiome. Dysbiosis indexes were constructed based on the characteristic high-dimensional biomarkers identified in the fecal microbiota from the three groups by linear discriminant analysis and generalized linear model analysis to quantify the dysbiosis of fecal microbiota. The effectiveness of α and β diversity indices and dysbiosis indexes was assessed in distinguishing the fecal microbiome among the three groups. The influences of serum inflammatory factors on gut microbiota were also addressed. The α diversity indices were significantly different between the three groups, the highest in HC group and the lowest in FRI group (P < 0.05). The β diversity indices showed significant phylogenetic dissimilarity of gut microbiome composition among the three groups (P < 0.001). The dysbiosis indexes were significantly higher in FRI group than in FH and HC groups (P < 0.001). The area under Receiver operating characteristic curve showed the characteristics of gut microbiota and the gut microbiota was found as effective in distinguishing the three groups. The dysbiosis in the FRI patients was associated with systemic inflammatory factors. In addition, significant differences in the gut microbiota were not observed between the FRI patients versus without sinus tract or pus before operation. Since FRI patients, with or without sinus tract or pus, have a characteristic profile of gut microbiota, their gut microbiota may be used as an auxiliary diagnostic tool for suspected FRI.